Early sequelae of post COVID-19 lung disease in patients who were mechanically ventilated for severe COVID-19 pneumonia - Singh, Nevadna (Department of Medicine, 2024)
Introduction: COVID-19 resulted in an unprecedented worldwide spike in hospital and ICU admissions; predominantly for adult respiratory distress syndrome (ARDS). Survival rates for patients requiring mechanical ventilation in Cape Town during the waves driven by the ancestral strain and beta variant were approximately 30% during the first 3 waves of the pandemic. However, post-ICU admission sequelae and recovery trajectory in sub-Saharan Africa remain unknown. Methods: We systematically evaluated a cohort of COVID-19 ICU survivors at three months following hospital discharge. A retrospective single-centre study enrolled all COVID-19 pneumonia patients who were admitted to ICU for mechanical ventilation and followed up at the post-COVID-19 Lung Disease Clinic between 1 July 2020 and 30 December 2021. Results: A total of 26 patients were evaluated at 3 months after discharge from hospital following mechanical ventilation: 53% were male and 81% had at least one co-morbidity. Diabetes and hypertension were present in 42% and 54% of patients respectively. Persistent dyspnoea (89%) and fatigue (54%) were the most common post-COVID-19 symptoms. Median FEV1 and FVC were 73% (IQR 65-83) and 71% (IQR 61-77) of predicted values respectively, whilst median DLCO was 59% (IQR 41- 70) of predicted values. Abnormalities were confirmed in all patients (24/26) who underwent high resolution computer tomography (HRCT) of the chest, with ground glass opacities (46%) and interstitial thickening (58%) being most common. No significant risk factors for post-COVID-19 impairment were identified. Conclusion: At 3 months after hospitalization, patients who received mechanical ventilation for COVID-19 pneumonia frequently reported ongoing symptoms. Lung function was moderately impaired with a disproportionate reduction in DLCO, and radiographic abnormalities were common. Long term follow up is required to determine the natural history post severe-COVID-19 lung disease.